2023
DOI: 10.3389/fphar.2023.1160616
|View full text |Cite
|
Sign up to set email alerts
|

An updated pharmacological insight into calotropin as a potential therapeutic agent in cancer

Abstract: Calotropin is a pharmacologically active compound isolated from milkweed plants like Calotropis procera, Calotropis gigantea, and Asclepias currasavica that belong to the Asclepiadaceae family. All of these plants are recognised as medical traditional plants used in Asian countries. Calotropin is identified as a highly potent cardenolide that has a similar chemical structure to cardiac glycosides (such as digoxin and digitoxin). During the last few years, cytotoxic and antitumor effects of cardenolides glycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Since 2010, there has been considerable focus on studying the anticancer effects of C. gigantea extracts in many cancer models [25,26,[38][39][40][41]. However, biological activities involving C. gigantea stem bark extracts have rarely been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, there has been considerable focus on studying the anticancer effects of C. gigantea extracts in many cancer models [25,26,[38][39][40][41]. However, biological activities involving C. gigantea stem bark extracts have rarely been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…1 × 10 5 HSC-3 cells were sown in each well of 96-well plates, and grown for 24 h and treated for 24 and 48 h. The glucose uptake test colorimetric kit was used in accordance with the directions provided by the manufacturer to measure glucose uptake. A pre-treatment with 5 mM and 10 mM d -glucose (2-DG) was given to HSC-3 cells at a population of 1 × 10 5 cells for 6 h before the intended drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Plant-based natural remedies have the potential to provide therapies with fewer adverse reactions and equivalent or greater efficacy. 4 , 5 Medicinal plants have long been used in treating various diseases, including cancer, and they remain an essential resource for finding new drugs. 6 Despite their potential, many plants have yet to be thoroughly investigated for their anti-cancer activity specifically against oral squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…[58] Calotropin's IC 50 value on the human hepatocarcinoma cell line (HepG 2 ) and Raji cells (human B lymphoblastoid cell line) was revealed in a study, and values were reported as 0.04 µM and 0.02 µM, respectively; this validated the drug's cytotoxic action on tumor cell lines. [11,[59][60][61]…”
Section: Calotropin Is Employed Solely To Combat Breast Cancermentioning
confidence: 99%
“…Calotropin is a highly potent cardenolide with a chemical composition equivalent to cardiac glycosides (such as digoxin and digitoxin). [9][10][11][12][13] Both species are widespread. However, Calotropis procera is more prevalent and has purple blooms, whereas Calotropis gigantea has whitish flowers.…”
Section: Introductionmentioning
confidence: 99%